Binocular vision therapy for the treatment of Amblyopia—A review - Isha Chaturvedi; Rana Jamil; Pradeep Sharma (Indian Journal of Ophthalmology, 2023)
Amblyopia is a monocular or binocular reduction in visual acuity that results from prolonged visual deprivation in the early years of life. It is second only to refractive error as a cause of poor vision in children. The gold standard treatment of amblyopia includes patching and, less commonly, atropine penalization and filters. These therapies are aimed at improvements in the visual acuity of the amblyopic eye alone. They have compliance and psychosocial issues and gains are accrued after prolonged periods. Experimental studies have demonstrated the presence of binocular cortical communication even in amblyopes and neural plasticity in late childhood as well as adulthood. On this basis, binocular vision therapy aimed at the stimulation of both eyes rather than forced use of the amblyopic eye was developed. Such therapies involve visual tasks designed in such a way that they can be completed only by binocular viewing. These tasks vary from simple game play using red-green glasses, to engaging 3D games and movie viewing. Preliminary data suggest that binocular vision therapy has led to lasting improvements in visual acuity and can be a useful adjunct, if not replacement, to the conventional treatment of amblyopia. In this article, we aim to describe the various binocular vision therapies and review the available literature on the same.